2019
DOI: 10.1161/jaha.119.013592
|View full text |Cite
|
Sign up to set email alerts
|

Does Race Influence Decision Making for Advanced Heart Failure Therapies?

Abstract: BackgroundRace influences medical decision making, but its impact on advanced heart failure therapy allocation is unknown. We sought to determine whether patient race influences allocation of advanced heart failure therapies.Methods and ResultsMembers of a national heart failure organization were randomized to clinical vignettes that varied by patient race (black or white man) and were blinded to study objectives. Participants (N=422) completed Likert scale surveys rating factors for advanced therapy allocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 33 publications
2
119
1
Order By: Relevance
“…Participant data were collected in 2010, and it is possible that professional perspectives have changed over the years. However, more recently published data have suggested that bias based on race and ethnicity not only persists but influences decision making in health care settings similar to those in which recruitment for clinical trials takes place . Although the stakeholder data corresponded to only some of the data in the previous literature, we cannot rule out the possibility that stakeholders' views are informed both by their personal experience and previously published literature regarding racial disparities in clinical trial participation.…”
Section: Discussionmentioning
confidence: 77%
“…Participant data were collected in 2010, and it is possible that professional perspectives have changed over the years. However, more recently published data have suggested that bias based on race and ethnicity not only persists but influences decision making in health care settings similar to those in which recruitment for clinical trials takes place . Although the stakeholder data corresponded to only some of the data in the previous literature, we cannot rule out the possibility that stakeholders' views are informed both by their personal experience and previously published literature regarding racial disparities in clinical trial participation.…”
Section: Discussionmentioning
confidence: 77%
“…Women are diagnosed and referred for advanced HF therapies later in the course of their disease, which may be due to atypical disease presentations, but may also be due to implicit bias on the part of providers. 7,36 A recent analysis by Breathett et al 37 confirms that implicit bias does influence decision making for advanced HF therapies. Bias may be particularly important for women who are attempting to access advanced HF therapies, since the psychosocial and socioeconomic determinants of health may have a greater impact on women than men.…”
Section: Discussionmentioning
confidence: 97%
“…Conversations rather than surveys guide these allocation meetings, and more dominant members may lead the conversations and control the final decision. 7 In addition, the differences in concerns by gender and race could contribute to a delay in treatment, which could worsen outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Association of Gender and Race With Allocation of Advanced Heart Failure Therapies purposefully selected for diversity of participant demographic characteristics (ie, gender, race, geography, and years past training). Snowball sampling was used to meet an enrollment goal of 44 participants because it was sufficient to reach 1:1 thematic saturation in a prior study 7 and snowball sampling is an established method of recruiting specific hard-to-reach subgroups. 14…”
Section: Jama Network Open | Cardiologymentioning
confidence: 99%